MOSCOW AS ONE OF THE COORDINATES IN THE FORMATION OF REGIONAL IDENTITY IN RUSSIA - Podvintzev, O.B. (Perm Federal Research Centre Journal, 2015)
According to the author, the formation of regional identity in modern Russia requires to position the region in relation to the past and future of Russia, its main parts, the neighboring subjects of the Federation, as well as Moscow (not only as the capital).